DOES SOCIAL MEDIA MARKETING DRIVE INDONESIAN CUSTOMER LOYALTY FOR ECO-BEAUTY PRODUCTS? - Nicholas Dwi Chandra; Karto Adiwijaya (Jurnal Apresiasi Ekonomi, 2025)
Social media marketing activities of eco-beauty products is widely used by many businesses in Indonesia to increase the society’s environmental awareness and purchase intention. However, the customer loyalty for such product is still relatively low. This research aims to analyze the effect of social media marketing (SMM) on customer loyalty, particularly for eco-beauty products continuous purchase intention (CPI). The research extends the Theory of Planned Behavior (TPB) by integrating the model with the Stimulus-Organism-Response (SOR) Theory, with the addition of SMM as the antecedent, and perceived green product knowledge (GPK), environmental concern (ENC), and satisfaction (SAT) as mediators. The research is performed in Indonesia using questionnaire targeted to active social media users aged 18-44 that have previously purchased eco-beauty products. The data obtained is analyzed using PLS-SEM method. The results show that SMM has no direct effect on CPI. However, SMM has significant positive effects on CPI through the mediation of GPK, ENC, all TPB dimensions, and SAT. This research offers theoretical contribution by elucidating the influence of SMM on customer loyalty for eco-beauty products based on the extension of TPB model. Practically, this research offers insights on creating the effective SMM strategy to boost eco-beauty products continuous purchase.